Modified ZSM-5 molecular sieve and preparation method thereof, light hydrocarbon cracking catalyst and preparation method thereof
By synthesizing ultra-thin phosphorus-containing ZSM-5 molecular sieve by using organophosphorus source and F-assisted crystallization method, the problems of limited reaction conversion and diene selectivity caused by narrowing the pore structure of traditional ZSM-5 molecular sieve are solved, and the effect of improving the catalytic reaction efficiency and activity of light hydrocarbon cracking is achieved.
Patent Information
- Application Number
- CN202411926455.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
Due to the narrow pore structure of traditional ZSM-5 molecular sieve, the reaction conversion rate and diene selectivity in light hydrocarbon cracking catalytic reaction are limited.
Ultra-thin phosphorus-containing ZSM-5 molecular sieve was synthesized by organic phosphorus source and F-assisted crystallization method. By reducing the diffusion path along the straight pore (b axis), diffusion resistance is reduced, thereby improving the mass transfer rate of reaction intermediates and products.
The diene yield and reaction conversion rate of light hydrocarbon cracking catalytic reaction are improved, the formation of coke is reduced, and the activity of the catalyst is enhanced.
Smart Images

Figure BDA0005209360430000121 
Figure BDA0005209360430000131 
Figure BDA0005209360430000132
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical industry, and in particular to a modified ZSM-5 molecular sieve and a preparation method thereof, a light hydrocarbon cracking catalyst and a preparation method thereof. Background Art
[0002] Zeolite is an aluminosilicate crystal synthesized by silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron through oxygen bridges. Among them, ZSM-5 zeolite has attracted extensive attention in the field of light hydrocarbon cracking due to its unique acid sites, pore structure and hydrothermal stability. However, the traditional ZSM-5 molecular sieve has a narrow pore structure, a long molecular diffusion path, and limited diffusion, which in turn limits the reaction conversion rate and diene selectivity in the light hydrocarbon cracking catalytic reaction. Summary of the invention
[0003] In view of this, the present invention provides a modified ZSM-5 molecular sieve and a preparation method thereof, a light hydrocarbon cracking catalyst and a preparation method thereof. The modified ZSM-5 molecular sieve provided by the present invention can effectively improve the diene yield of the light hydrocarbon cracking catalytic reaction.
[0004] The present invention provides a method for preparing a modified ZSM-5 molecular sieve, comprising the following steps:
[0005] A) mixing an aluminum source, water, a template and a silicon source to obtain an initial gel;
[0006] B) heating the initial gel obtained in step A) to pre-crystallize the gel to obtain a pre-crystallized gel;
[0007] C) mixing the pre-crystallized gel obtained in step B) with a phosphorus source and ammonium fluoride, and performing a heating crystallization treatment to obtain a crystallized molecular sieve;
[0008] D) calcining the crystallized molecular sieve obtained in step C) to obtain a modified ZSM-5 molecular sieve.
[0009] Preferably, in step C), the phosphorus source is at least one of triethylphosphine oxide, tripropylphosphine oxide and tributylphosphine oxide.
[0010] Preferably, the molar ratio of P in the phosphorus source to Si in the silicon source is (0.04-0.24):1;
[0011] The molar ratio of the ammonium fluoride to Si in the silicon source is (0.3-0.8):1.
[0012] Preferably, in step B), the temperature of the heating pre-crystallization treatment is 80-90° C. and the time is 12-18 hours.
[0013] Preferably, in step C), the temperature of the heating crystallization treatment is 150-180° C. and the time is 24-72 hours.
[0014] Preferably, in step D), the calcination temperature is 550-700° C. and the calcination time is 4-6 hours.
[0015] Preferably, the aluminum source is aluminum hydroxide and / or aluminum sulfate;
[0016] The template agent is at least one of tetrapropylammonium hydroxide, n-butylamine and tetrapropylammonium bromide;
[0017] The silicon source is at least one of silica gel, tetraethyl orthosilicate and silica sol;
[0018] The molar ratio of Si in the silicon source to Al in the aluminum source is (15-60):1;
[0019] The molar ratio of Si to the template in the silicon source is 1:(0.05-0.2);
[0020] The molar ratio of Si to water in the silicon source is 1:(20-40).
[0021] The present invention also provides a modified ZSM-5 molecular sieve, which is prepared by the preparation method described in the above technical solution.
[0022] The present invention also provides a light hydrocarbon cracking catalyst, the raw materials for its preparation include, by weight:
[0023] Molecular sieve 400 parts;
[0024] 500-700 parts of kaolin;
[0025] 100-150 parts of aluminum sol;
[0026] Phosphoric acid 50-100 parts;
[0027] 100-150 parts of silica sol;
[0028] Wherein, the molecular sieve is the modified ZSM-5 molecular sieve described in the above technical solution.
[0029] The present invention also provides a method for preparing the light hydrocarbon cracking catalyst described in the above technical solution, comprising the following steps:
[0030] S1, mixing kaolin, aluminum sol, phosphoric acid, molecular sieve and silica sol to obtain a slurry;
[0031] S2, spray-drying the slurry to obtain microsphere particles;
[0032] S3, calcining the microsphere particles to obtain a light hydrocarbon cracking catalyst.
[0033] Compared with the 0.53×0.56nm sinusoidal channels in ZSM-5 zeolite, the 0.51×0.55nm straight channels have better diffusion efficiency; therefore, reducing the diffusion path along the straight channels (b axis) is an effective method to increase the mass transfer rate of reaction intermediates and products. - Ultra-thin phosphorus-containing ZSM-5 molecular sieve crystals were synthesized by the assisted crystallization method. No Na+ ions were introduced during the preparation process, so no additional ion exchange process was required. The phosphorus-modified ZSM-5 molecular sieve was obtained by directly calcining the obtained solid. The obtained phosphorus-modified ZSM-5 molecular sieve has the characteristics of high specific surface area, rich pore structure, and short b-axis. It can reduce the diffusion path along the straight pore (b-axis) and reduce the diffusion resistance, thereby increasing the mass transfer rate of reaction intermediates and products. The method is simple to operate and the steps are simple. The synthesized material can be directly applied to the catalytic reaction of light hydrocarbon cracking, which is beneficial to improving the reaction conversion rate and diene selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0035] Figure 1 The XRD spectra of the ZSM-5 molecular sieves obtained in Example 1 and Comparative Example 1 are shown in FIG.
[0036] Figure 2 The SEM images of the ZSM-5 molecular sieves obtained in Example 1 and Comparative Example 1 are shown in FIG. Figure 2 (a) is a SEM image of the ZSM-5 molecular sieve obtained in Example 1, Figure 2 (b) is the SEM image of the ZSM-5 molecular sieve obtained in Comparative Example 1. DETAILED DESCRIPTION
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0038] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0039] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0040] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0041] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 80-90℃ means that the units of the left endpoint "80" and the right endpoint "90" are both ℃.
[0042] The present invention provides a method for preparing a modified ZSM-5 molecular sieve, comprising the following steps:
[0043] A) mixing an aluminum source, water, a template and a silicon source to obtain an initial gel;
[0044] B) heating the initial gel obtained in step A) to pre-crystallize the gel to obtain a pre-crystallized gel;
[0045] C) mixing the pre-crystallized gel obtained in step B) with a phosphorus source and ammonium fluoride, and performing a heating crystallization treatment to obtain a crystallized molecular sieve;
[0046] D) calcining the crystallized molecular sieve obtained in step C) to obtain a modified ZSM-5 molecular sieve.
[0047] [About Step A]:
[0048] A) Mix aluminum source, water, template and silicon source to obtain an initial gel.
[0049] In the present invention, the aluminum source is preferably aluminum hydroxide and / or aluminum sulfate.
[0050] In the present invention, the template agent is preferably at least one of tetrapropylammonium hydroxide, n-butylamine and tetrapropylammonium bromide.
[0051] In the present invention, the silicon source is preferably at least one of silica gel, tetraethyl orthosilicate and silica sol.
[0052] In the present invention, the molar ratio of Si in the silicon source to Al in the aluminum source is preferably (15-60):1, specifically 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1.
[0053] In the present invention, the molar ratio of Si in the silicon source to the template is preferably 1:(0.05-0.2), specifically 1:0.05, 1:0.10, 1:0.15, 1:0.20.
[0054] In the present invention, the molar ratio of Si to water in the silicon source is preferably 1:(20-40), specifically 1:20, 1:25, 1:30, 1:35, 1:40.
[0055] In the present invention, step A) preferably specifically comprises:
[0056] A1) mixing an aluminum source with water to obtain a solution 1;
[0057] A2) mixing the solution 1 with a template to obtain a solution 2;
[0058] A3) Mixing the solution 2 with a silicon source to obtain an initial gel.
[0059] The present invention first mixes an aluminum source with water and stirs them evenly to obtain a solution 1. Then, a template is added to the solution 1 and mixed evenly to obtain a solution 2. Finally, a silicon source is added to the solution 2 and stirred to form a gel. The present invention has no particular restrictions on the temperature conditions for the above steps A1) to A3), and they can be performed at room temperature.
[0060] [About step B]:
[0061] B) heating the initial gel obtained in step A) for pre-crystallization to obtain a pre-crystallized gel.
[0062] In the present invention, the heating pre-crystallization treatment is a low-temperature pre-crystallization treatment, and the temperature is preferably 80-90°C, specifically 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C. The heating pre-crystallization treatment time is preferably 12-18h, specifically 12h, 13h, 14h, 15h, 16h, 17h, 18h. Through the above-mentioned low-temperature pre-crystallization treatment, more structural unit fragments are formed in the initial gel obtained in step A), and the appearance is still a viscous gel state.
[0063] [About Step C]:
[0064] C) mixing the pre-crystallized gel obtained in step B) with a phosphorus source and ammonium fluoride, and performing a heating crystallization treatment to obtain a crystallized molecular sieve.
[0065] In the present invention, the phosphorus source is preferably at least one of triethylphosphine oxide, tripropylphosphine oxide and tributylphosphine oxide. In the present invention, the molar ratio of P in the phosphorus source to Si in the silicon source is preferably (0.04-0.24):1, specifically 0.04:1, 0.05:1, 0.10:1, 0.15:1, 0.20:1, 0.24:1.
[0066] In the present invention, the molar ratio of the ammonium fluoride to Si in the silicon source is preferably (0.3-0.8):1, specifically 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1.
[0067] In the present invention, the pre-crystallized gel obtained in step B) is mixed with a phosphorus source and ammonium fluoride, and then subjected to a heating crystallization treatment. Compared with the low-temperature heating pre-crystallization treatment in step B), the heating crystallization treatment is a high-temperature crystallization treatment, and the temperature is preferably 150 to 180°C, specifically 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C. The time of the heating crystallization treatment is preferably 24 to 72h, specifically 24h, 36h, 48h, 60h, 72h. After the above-mentioned heating crystallization treatment, a crystallized molecular sieve is obtained.
[0068] [About Step D]:
[0069] D) calcining the crystallized molecular sieve obtained in step C) to obtain a modified ZSM-5 molecular sieve.
[0070] In the present invention, before the calcination, the crystallized molecular sieve obtained in step C) is preferably filtered and dried. The filtration is preferably suction filtration to obtain a solid. After filtering out the solid, it is dried. The drying temperature is preferably 60 to 100°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C; the drying time is preferably 6 to 12h, specifically 6h, 7h, 8h, 9h, 10h, 11h, 12h. After the above treatment, calcination is performed.
[0071] In the present invention, the calcination temperature is preferably 550-700°C, specifically 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C. The calcination time is preferably 4-6h, specifically 4h, 5h, 6h. After the above calcination, a modified ZSM-5 molecular sieve is obtained, specifically an ultra-thin phosphorus-containing ZSM-5 molecular sieve.
[0072] The present invention also provides a modified ZSM-5 molecular sieve prepared by the preparation method described in the above technical solution.
[0073] Compared with the 0.53×0.56nm sinusoidal channels in ZSM-5 zeolite, the 0.51×0.55nm straight channels have better diffusion efficiency; therefore, reducing the diffusion path along the straight channels (b axis) is an effective method to increase the mass transfer rate of reaction intermediates and products. - Ultra-thin phosphorus-containing ZSM-5 molecular sieve crystals were synthesized by the assisted crystallization method. No Na+ ions were introduced during the preparation process, so no additional ion exchange process was required. The phosphorus-modified ZSM-5 molecular sieve was obtained by directly calcining the obtained solid. The obtained phosphorus-modified ZSM-5 molecular sieve has the characteristics of high specific surface area, rich pore structure, and short b-axis. It can reduce the diffusion path along the straight pore (b-axis) and reduce the diffusion resistance, thereby increasing the mass transfer rate of reaction intermediates and products. The method is simple to operate and the steps are simple. The synthesized material can be directly applied to the catalytic reaction of light hydrocarbon cracking, which is beneficial to improving the reaction conversion rate and diene selectivity.
[0074] The present invention also provides a light hydrocarbon cracking catalyst, the raw materials for its preparation include, by weight:
[0075] Molecular sieve 400 parts;
[0076] 500-700 parts of kaolin;
[0077] 100-150 parts of aluminum sol;
[0078] Phosphoric acid 50-100 parts;
[0079] 100-150 parts of silica sol;
[0080] Wherein, the molecular sieve is the modified ZSM-5 molecular sieve described in the above technical solution.
[0081] The amount of kaolin used can be 500 parts, 550 parts, 600 parts, 650 parts, 700 parts, and more preferably 600 parts. The amount of aluminum sol used can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, and more preferably 130 parts. The amount of phosphoric acid used can be 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts. The amount of silica sol used can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, and more preferably 130 parts.
[0082] The present invention also provides a method for preparing the light hydrocarbon cracking catalyst described in the above technical solution, comprising the following steps:
[0083] S1, mixing kaolin, aluminum sol, phosphoric acid, molecular sieve and silica sol to obtain a slurry;
[0084] S2, spray-drying the slurry to obtain microsphere particles;
[0085] S3, calcining the microsphere particles to obtain a light hydrocarbon cracking catalyst;
[0086] Among them, the types and amounts of kaolin, aluminum sol, phosphoric acid, molecular sieve and silica sol are consistent with those described in the previous technical solution, and will not be repeated here.
[0087] Regarding step S1: The mixing method is preferably to stir and mix first, and then ball mill. The materials are mixed by stirring to obtain a slurry, and then the slurry is ball milled. The speed of the ball mill is preferably 400-1000rpm, specifically 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm; the time of the ball mill is preferably 1-3h, specifically 1h, 2h, 3h.
[0088] Regarding step S2: After the slurry is obtained in step S1, it is sent to a spray dryer for spray molding. The present invention has no special restrictions on spray drying molding, and it can be carried out according to the conventional methods and conditions in the field. Microsphere particles are obtained by spray drying molding. The particle size distribution of the obtained microsphere particles is 20 to 800 μm.
[0089] Regarding step S3: the calcination temperature is preferably 400-600°C, specifically 400°C, 450°C, 500°C, 550°C, 600°C. The calcination time is preferably 4-6h, specifically 4h, 5h, 6h. After calcination, a light hydrocarbon cracking catalyst is obtained.
[0090] The present invention uses kaolin, aluminum sol, phosphoric acid, molecular sieve and silica sol as raw materials, wherein the molecular sieve is an active ingredient, and kaolin is used as a matrix of the catalyst. After being acidified with phosphoric acid, the kaolin can produce more pores, and the matrix and the active ingredient are bonded together by silica sol and aluminum sol. An atomizer is used to spray them into spherical particles, and finally the components are tightly connected by roasting to finally obtain a spherical light hydrocarbon cracking catalyst.
[0091] The present invention also provides an application of the light hydrocarbon cracking catalyst described in the above technical solution in the preparation of olefins by cracking light hydrocarbons.
[0092] The present invention also provides a method for preparing olefins by cracking light hydrocarbons, wherein the catalyst used is the light hydrocarbon cracking catalyst described in the above technical solution.
[0093] The present invention uses the above molecular sieve as the active ingredient in the light hydrocarbon cracking catalyst, and exhibits excellent diene selectivity in the light hydrocarbon cracking reaction. The light hydrocarbon catalytic cracking catalyst provided by the present invention can improve the reaction substrate diffusion rate, reaction conversion rate and diene selectivity, and is particularly suitable for the field of producing more dienes in light hydrocarbon cracking in refineries.
[0094] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. In the following examples, the silica sol is a silica sol with a solid content of 30%. The aluminum sol is a silica sol with a solid content of 10%.
[0095] Example 1
[0096] 1. Preparation of ultra-thin phosphorus-containing ZSM molecular sieve
[0097] A) Preparation of initial gel:
[0098] A1) 0.25 mol of aluminum hydroxide was added to 300 mol of water and stirred to obtain solution 1.
[0099] A2) 0.75 mol of tetrapropylammonium bromide was added to solution 1 to obtain solution 2.
[0100] A3) 15 mol of silica gel was added to solution 2 to obtain an initial gel.
[0101] B) The initial gel obtained in step A) was transferred to a round-bottom flask and pre-crystallized at 80° C. for 12 h to obtain a pre-crystallized gel.
[0102] C) After adding 0.3 mol of triethylphosphine oxide and 4.5 mol of ammonium fluoride to the pre-crystallized gel obtained in step B), the mixture was transferred to a reaction kettle and crystallized at 150° C. for 72 hours to obtain a crystallized molecular sieve.
[0103] D) The crystallized molecular sieve obtained in step C) is filtered to remove the solid, dried at 60° C. for 8 h, and then calcined at 550° C. for 6 h to obtain an ultra-thin phosphorus-containing ZSM-5 molecular sieve.
[0104] 2. Preparation of light hydrocarbon cracking catalyst
[0105] S1. 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of ZSM-5 molecular sieve and 130 g of silica sol were added in order, mixed and stirred into a slurry, and then ball-milled to obtain a slurry.
[0106] S2, spraying the obtained slurry in a spray dryer to obtain microsphere particles.
[0107] S3. The obtained microsphere particles are calcined at 500° C. for 2 h to obtain a light hydrocarbon cracking catalyst.
[0108] Example 2
[0109] 1. Preparation of ultra-thin phosphorus-containing ZSM molecular sieve
[0110] A) Preparation of initial gel:
[0111] A1) 0.25 mol of aluminum sulfate was added to 300 mol of water and stirred to obtain solution 1.
[0112] A2) 3 mol of n-butylamine was added to solution 1 to obtain solution 2.
[0113] A3) 50 mol of silica sol with a solid content of 30% was added to solution 2 to obtain an initial gel.
[0114] B) The initial gel obtained in step A) was transferred to a round-bottom flask and pre-crystallized at 90° C. for 18 h to obtain a pre-crystallized gel.
[0115] C) After adding 0.3 mol of tripropylphosphine oxide and 12 mol of ammonium fluoride to the pre-crystallized gel obtained in step B), the mixture was transferred to a reaction kettle and crystallized at 180° C. for 24 hours to obtain a crystallized molecular sieve.
[0116] D) The crystallized molecular sieve obtained in step C) is filtered to remove the solid, dried at 60° C. for 8 h, and then calcined at 700° C. for 4 h to obtain an ultra-thin phosphorus-containing ZSM-5 molecular sieve.
[0117] 2. Preparation of light hydrocarbon cracking catalyst
[0118] S1. 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of ZSM-5 molecular sieve and 130 g of silica sol were added in order, mixed and stirred into a slurry, and then ball-milled to obtain a slurry.
[0119] S2, spraying the obtained slurry in a spray dryer to obtain microsphere particles.
[0120] S3. The obtained microsphere particles are calcined at 500° C. for 2 h to obtain a light hydrocarbon cracking catalyst.
[0121] Example 3
[0122] 1. Preparation of ultra-thin phosphorus-containing ZSM molecular sieve
[0123] A) Preparation of initial gel:
[0124] A1) 1 mol of aluminum hydroxide was added to 300 mol of water and stirred to obtain solution 1.
[0125] A2) 0.75 mol of tetrapropylammonium hydroxide was added to solution 1 to obtain solution 2.
[0126] A3) 15 mol of tetraethyl orthosilicate was added to solution 2 to obtain an initial gel.
[0127] B) The initial gel obtained in step A) was transferred to a round-bottom flask and pre-crystallized at 80° C. for 12 h to obtain a pre-crystallized gel.
[0128] C) After adding 0.3 mol of tributylphosphine oxide and 4.5 mol of ammonium fluoride to the pre-crystallized gel obtained in step B), the mixture was transferred to a reaction kettle and crystallized at 150° C. for 72 hours to obtain a crystallized molecular sieve.
[0129] D) The crystallized molecular sieve obtained in step C) is filtered to remove the solid, dried at 60° C. for 8 h, and then calcined at 550° C. for 4 h to obtain an ultra-thin phosphorus-containing ZSM-5 molecular sieve.
[0130] 2. Preparation of light hydrocarbon cracking catalyst
[0131] S1. 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of ZSM-5 molecular sieve and 130 g of silica sol were added in order, mixed and stirred into a slurry, and then ball-milled to obtain a slurry.
[0132] S2, spraying the obtained slurry in a spray dryer to obtain microsphere particles.
[0133] S3. The obtained microsphere particles are calcined at 500° C. for 2 h to obtain a light hydrocarbon cracking catalyst.
[0134] Example 4
[0135] 1. Preparation of ultra-thin phosphorus-containing ZSM molecular sieve
[0136] A) Preparation of initial gel:
[0137] A1) 1 mol of aluminum hydroxide was added to 300 mol of water and stirred to obtain solution 1.
[0138] A2) 0.75 mol of tetrapropylammonium hydroxide was added to solution 1 to obtain solution 2.
[0139] A3) 15 mol of tetraethyl orthosilicate was added to solution 2 to obtain an initial gel.
[0140] B) The initial gel obtained in step A) was transferred to a round-bottom flask and pre-crystallized at 80° C. for 12 h to obtain a pre-crystallized gel.
[0141] C) After adding 0.6 mol of tributylphosphine oxide and 4.5 mol of ammonium fluoride to the pre-crystallized gel obtained in step B), the mixture was transferred to a reaction kettle and crystallized at 150° C. for 72 hours to obtain a crystallized molecular sieve.
[0142] D) The crystallized molecular sieve obtained in step C) is filtered to remove the solid, dried at 60° C. for 8 h, and then calcined at 550° C. for 4 h to obtain an ultra-thin phosphorus-containing ZSM-5 molecular sieve.
[0143] 2. Preparation of light hydrocarbon cracking catalyst
[0144] S1. 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of ZSM-5 molecular sieve and 130 g of silica sol were added in order, mixed and stirred into a slurry, and then ball-milled to obtain a slurry.
[0145] S2, spraying the obtained slurry in a spray dryer to obtain microsphere particles.
[0146] S3. The obtained microsphere particles are calcined at 500° C. for 2 h to obtain a light hydrocarbon cracking catalyst.
[0147] Example 5
[0148] 1. Preparation of ultra-thin phosphorus-containing ZSM molecular sieve
[0149] A) Preparation of initial gel:
[0150] A1) 1 mol of aluminum hydroxide was added to 300 mol of water and stirred to obtain solution 1.
[0151] A2) 0.75 mol of tetrapropylammonium hydroxide was added to solution 1 to obtain solution 2.
[0152] A3) 15 mol of tetraethyl orthosilicate was added to solution 2 to obtain an initial gel.
[0153] B) The initial gel obtained in step A) was transferred to a round-bottom flask and pre-crystallized at 80° C. for 12 h to obtain a pre-crystallized gel.
[0154] C) After adding 1.2 mol of tributylphosphine oxide and 4.5 mol of ammonium fluoride to the pre-crystallized gel obtained in step B), the mixture was transferred to a reaction kettle and crystallized at 150° C. for 72 hours to obtain a crystallized molecular sieve.
[0155] D) The crystallized molecular sieve obtained in step C) is filtered to remove the solid, dried at 60° C. for 8 h, and then calcined at 550° C. for 4 h to obtain an ultra-thin phosphorus-containing ZSM-5 molecular sieve.
[0156] 2. Preparation of light hydrocarbon cracking catalyst
[0157] S1. 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of ZSM-5 molecular sieve and 130 g of silica sol were added in order, mixed and stirred into a slurry, and then ball-milled to obtain a slurry.
[0158] S2, spraying the obtained slurry in a spray dryer to obtain microsphere particles.
[0159] S3. The obtained microsphere particles are calcined at 500° C. for 2 h to obtain a light hydrocarbon cracking catalyst.
[0160] Example 6
[0161] 1. Preparation of ultra-thin phosphorus-containing ZSM molecular sieve
[0162] A) Preparation of initial gel:
[0163] A1) 1 mol of aluminum hydroxide was added to 300 mol of water and stirred to obtain solution 1.
[0164] A2) 0.75 mol of tetrapropylammonium hydroxide was added to solution 1 to obtain solution 2.
[0165] A3) 15 mol of tetraethyl orthosilicate was added to solution 2 to obtain an initial gel.
[0166] B) The initial gel obtained in step A) was transferred to a round-bottom flask and pre-crystallized at 80° C. for 12 h to obtain a pre-crystallized gel.
[0167] C) After adding 1.8 mol of tributylphosphine oxide and 4.5 mol of ammonium fluoride to the pre-crystallized gel obtained in step B), the mixture was transferred to a reaction kettle and crystallized at 150° C. for 72 hours to obtain a crystallized molecular sieve.
[0168] D) The crystallized molecular sieve obtained in step C) is filtered to remove the solid, dried at 60° C. for 8 h, and then calcined at 550° C. for 4 h to obtain an ultra-thin phosphorus-containing ZSM-5 molecular sieve.
[0169] 2. Preparation of light hydrocarbon cracking catalyst
[0170] S1. 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of ZSM-5 molecular sieve and 130 g of silica sol were added in order, mixed and stirred into a slurry, and then ball-milled to obtain a slurry.
[0171] S2, spraying the obtained slurry in a spray dryer to obtain microsphere particles.
[0172] S3. The obtained microsphere particles are calcined at 500° C. for 2 h to obtain a light hydrocarbon cracking catalyst.
[0173] Comparative Example 1
[0174] 1. Preparation of ZSM molecular sieve
[0175] The implementation is carried out in accordance with Example 3, except that the pre-crystallization treatment in step B) is not performed, and at the same time, the phosphorus source and ammonium fluoride are not introduced during the crystallization treatment in step C). The details are as follows:
[0176] A) Preparation of initial gel:
[0177] A1) 1 mol of aluminum hydroxide was added to 300 mol of water and stirred to obtain solution 1.
[0178] A2) 0.75 mol of tetrapropylammonium hydroxide was added to solution 1 to obtain solution 2.
[0179] A3) 15 mol of tetraethyl orthosilicate was added to solution 2 to obtain an initial gel.
[0180] C) The initial gel obtained in step A) is transferred to a reactor and crystallized at 150° C. for 72 hours to obtain a crystallized molecular sieve.
[0181] D) The crystallized molecular sieve obtained in step C) is filtered to remove the solid, dried at 60° C. for 8 h, and then calcined at 550° C. for 4 h to obtain a ZSM-5 molecular sieve.
[0182] 2. Preparation of light hydrocarbon cracking catalyst
[0183] S1. 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of ZSM-5 molecular sieve and 130 g of silica sol were added in order, mixed and stirred into a slurry, and then ball-milled to obtain a slurry.
[0184] S2, spraying the obtained slurry in a spray dryer to obtain microsphere particles.
[0185] S3. The obtained microsphere particles are calcined at 500° C. for 2 h to obtain a light hydrocarbon cracking catalyst.
[0186] Product Testing :
[0187] (1) XRD test
[0188] XRD tests were performed on the ZSM-5 molecular sieves obtained in Example 1 and Comparative Example 1, and the results are as follows: Figure 1 It can be seen that, compared with the standard MFI diffraction peak spectrum, both Example 1 and Comparative Example 1 have and only have characteristic diffraction peaks of the MFI phase, indicating that the materials prepared by the two preparation methods are both ZSM-5 molecular sieves.
[0189] (2) SEM characterization
[0190] The ZSM-5 molecular sieves obtained in Example 1 and Comparative Example 1 were tested for microscopic morphology (SEM), and the results are as follows: Figure 2 It can be seen that the ZSM-5 molecular sieve obtained in Comparative Example 1 has a plate-like structure, while the ZSM-5 molecular sieve obtained in Example 1 has an obvious lamellar structure and exhibits a thin sheet morphology, and is an ultra-thin molecular sieve.
[0191] (3) Molecular sieve specific surface area and pore volume test
[0192] The specific surface area and pore volume of the ZSM-5 molecular sieves obtained in Examples 1-6 and Comparative Example 1 were tested respectively. The results are shown in Table 1.
[0193] Table 1: Molecular sieve specific surface area and pore volume test results
[0194]
[0195] It can be seen from the specific surface area and pore volume tests in Table 1 that the modified ZSM-5 molecular sieves obtained in Examples 1-6 have a short b-axis and a specific surface area significantly higher than that of Comparative Example 1.
[0196] From the above test results, it can be seen that the modified ZSM-5 molecular sieve prepared in the present invention has the advantages of thin flake morphology, shortened b axis, high specific surface area, etc.
[0197] (4) Catalytic performance test
[0198] The crude oil shown in Table 2 is used as raw material and a catalyst is used to carry out catalytic cracking reaction to prepare olefins.
[0199] Table 2: Physical properties of crude oil
[0200]
[0201] The catalytic effects of the catalysts obtained in Examples 1-6 and Comparative Example 1 are shown in Table 3:
[0202] Table 3: Catalytic effects of catalysts in various examples and comparative examples
[0203]
[0204] It can be seen from the test results in Table 3 that compared with Comparative Example 1, the catalysts obtained in Examples 1-6 of the present invention have higher diene yields and lower coke. This is because the ZSM-5 molecular sieves prepared in Examples 1-6 have a higher specific surface area and a shorter b-axis, which improves the mass transfer rate of reactants and products in the light hydrocarbon cracking reaction, inhibits the occurrence of secondary reactions, and is beneficial to improving diene selectivity and inhibiting the formation of coke. In addition, in Examples 1-3, as the molecular sieve silicon-aluminum ratio decreases, the light hydrocarbon cracking conversion rate continues to increase; in Examples 3-6, as the amount of phosphorus introduced increases, the diene selectivity continues to increase.
[0205] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a modified ZSM-5 molecular sieve, characterized in that: The following steps are involved: A) mixing an aluminum source, water, a template and a silicon source to obtain an initial gel; B) heating the initial gel obtained in step A) to pre-crystallize the gel to obtain a pre-crystallized gel; C) mixing the pre-crystallized gel obtained in step B) with a phosphorus source and ammonium fluoride, and performing a heating crystallization treatment to obtain a crystallized molecular sieve; D) calcining the crystallized molecular sieve obtained in step C) to obtain a modified ZSM-5 molecular sieve.
2. The preparation method according to claim 1, characterized in that: In step C), the phosphorus source is at least one of triethylphosphine oxide, tripropylphosphine oxide and tributylphosphine oxide.
3. The preparation method according to claim 1, characterized in that: The molar ratio of P in the phosphorus source to Si in the silicon source is (0.04-0.24):1; The molar ratio of the ammonium fluoride to Si in the silicon source is (0.3-0.8):
1.
4. The preparation method according to claim 1, characterized in that: In step B), the temperature of the heating pre-crystallization treatment is 80-90° C. and the time is 12-18 hours.
5. The preparation method according to claim 1, characterized in that: In step C), the temperature of the heating crystallization treatment is 150-180° C. and the time is 24-72 hours.
6. The preparation method according to claim 1, characterized in that: In step D), the calcination temperature is 550-700° C. and the calcination time is 4-6 hours.
7. The preparation method according to claim 1, characterized in that: The aluminum source is aluminum hydroxide and / or aluminum sulfate; The template agent is at least one of tetrapropylammonium hydroxide, n-butylamine and tetrapropylammonium bromide; The silicon source is at least one of silica gel, tetraethyl orthosilicate and silica sol; The molar ratio of Si in the silicon source to Al in the aluminum source is (15-60):1; The molar ratio of Si to the template in the silicon source is 1:(0.05-0.2); The molar ratio of Si to water in the silicon source is 1:(20-40).
8. A modified ZSM-5 molecular sieve, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. A light hydrocarbon cracking catalyst, characterized in that: The raw materials for its preparation include, by weight: Wherein, the molecular sieve is the modified ZSM-5 molecular sieve described in claim 8.
10. A method for preparing the light hydrocarbon cracking catalyst according to claim 9, characterized in that: The following steps are involved: S1, mixing kaolin, aluminum sol, phosphoric acid, molecular sieve and silica sol to obtain a slurry; S2, spray-drying the slurry to obtain microsphere particles; S3, calcining the microsphere particles to obtain a light hydrocarbon cracking catalyst.